Randomized study comparing full dose monotherapy (S-1 followed by irinotecan) and reduced dose combination therapy (S-1/oxaliplatin followed by S-1/irinotecan) as initial therapy for older patients with metastatic colorectal cancer: NORDIC 9 - Stine Braendegaard Winther; Pia Österlund; Åke Berglund; Bengt Glimelius; Camilla Qvortrup; Halfdan Sorbye; Per Pfeiffer; - on behalf of the Academy of Geriatric Cancer Research (AgeCare) (BMC Cancer, 2017)
Abstract Background Metastatic colorectal cancer (mCRC) is a disease of older age, but there is a relative lack of knowledge about effects of chemotherapy in older patients as they are under-represented in clinical trials. Little data can guide whether the strategy in older mCRC patients should be a sequential full-dose monotherapy chemotherapy approach or a dose-reduced combination chemotherapy approach. The oral 5FU prodrug S-1 seems to have less side effects than capecitabine and should be an optimal drug for older patients, but few data are available. Improved geriatric assessments are needed to select which older patients should receive therapy. Methods The NORDIC 9 trial is a Nordic multicenter randomized phase II study comparing full dose monotherapy (S-1 30 mg/m2 twice daily days 1–14 every 3 weeks, followed by second line irinotecan 250–350 mg/m2 iv day 1 every 3 weeks or 180–250 mg/m2 iv day 1 every 2 weeks) with reduced dose combination therapy (S-1 20 mg/m2 days 1–14 + oxaliplatin 100 mg/m2 iv day 1 every 3 weeks, followed by second line S-1 20 mg/m2 days 1–14 + irinotecan 180 mg/m2 day 1 every 3 week) for older patients (≥70 years) with mCRC who are not candidates for full-dose standard combination therapy. Additional bevacizumab (7.5 mg/kg) is optional in first-line. Blood samples and tumor tissue will be collected to investigate predictive markers. Geriatric screening tools (G-8, VES-13, Timed-Up-and-Go and Handgrip strength), Charlson Comorbidty Index and quality of life (EORTC QLQ-C30) will be evaluated as predictors of efficacy and toxicity. The target sample size is 150 patients. The primary endpoint is progression-free survival and secondary endpoints are time-to-failure of strategy, overall survival, response rate, toxicity, and correlations between biomarkers, pre-treatment characteristics and geriatric assessments. Discussion The study will add knowledge on how to treat older mCRC patients who are not candidates for standard combination therapy. Furthermore it may provide understanding of efficacy and tolerability of chemotherapy in older cancer patients and thus offer a better chance for tailored treatment strategies in these patients. Trial registration EU Clinical Trial Register, EudraCT no. 2014–000394-39 . Registered 05 May 2014.